Factors associated with the development and severity of oxaliplatin‐induced peripheral neuropathy: a systematic review. Issue 6 (27th June 2017) - Pulvers, Jeremy N.; Marx, Gavin
Abstract: Oxaliplatin is a platinum‐derivative chemotherapeutic agent used for colorectal cancer in the adjuvant and metastatic setting in combination with folinic acid and 5‐fluorouracil. Oxaliplatin causes an acute cold‐induced neurotoxicity and a chronic cumulative neuropathy, which can require dose modification and impact quality of life. To date, no prevention and treatment strategies have proved effective thus reinforcing the importance of identifying at‐risk patients in order to maximize therapeutic benefit while minimizing neurotoxicity. Here we reviewed studies on risk and prognostic factors associated with the development and severity of oxaliplatin‐induced peripheral neuropathy. A systematic search was conducted in MEDLINE and Embase, and studies investigating clinical and patient‐related factors associated with oxaliplatin‐induced peripheral neuropathy as their primary focus were identified, and quantitative data were extracted when available. We identified 15 studies, of which only three were prospective. Notable factors were acute neurotoxicity symptoms predicting chronic neuropathy, baseline laboratory findings, patient demographics such as age and gender, comorbidities, and environmental factors. No factor was consistently identified across multiple studies other than the association with oxaliplatin dose. Further investigation into these factors may yield insight into potential neuropathy prevention and treatment strategies.